Characteristics And Seeds of Radiska (Raphanus sativus L.) - Habibullo Mamayoqubovich Kamolov (Zien Journals, 2021)
This article covers the beneficial properties of radishes for the human body, the amount of nutrients, the abundance of varieties suitable for cultivation, the cultivation of seed radishes and other features
Keywords: Radishes contain vitamins; nutrients; varieties of radishes; sufficient temperature for the plant